Microstructural analysis of nanostructured Zn O thin films - Urbina-Yarupetán, M.A. (2020)
We present the experimental results obtained from microstructural analysis of ZnO thin lms with20, 50, and 100 nm in thickness, grown onto the commercial glass substrate by reactive sputtering.We analyze the quantitative information on the size of the crystalline domains, the texture directionof the nanocolumns, their densities, thicknesses, surface and interface roughness obtained throughcharacterization techniques such as scanning electron microscope (SEM), X-ray reectivity (XRR)and X-ray diraction (DRX).